Manajemen Penguatan Pendidikan Karakter Gotong Royong di SD Negeri Bergas Lor 01 Kecamatan Bergas Kabupaten Semarang - Winarti, Tri; YSH, AY Soegeng; Egar, Ngasbun (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The aim of the research is to describe and analyze the planning, organization, implementation and supervision of strengthening mutual cooperation character education at SD Negeri Bergas Lor 01, Bergas District, Semarang Regency. This type of qualitative descriptive research, data collection through interviews, observation and documentation. Data analysis uses the Miles and Huberman model. Research results: (1) The planning stages include identifying and analyzing needs, determining goals, setting policies, preparing programs and outreach, (2) Organizing is carried out through optimizing resource utilization by dividing tasks, authority and responsibilities, (3) Implementation of strengthening character education mutual cooperation is integrated in intracurricular, co-curricular activities combined with P5, extracurricular, and habituation, (4) Supervision through monitoring and evaluation of all school activities. Monitoring is carried out continuously during program implementation. Evaluations are carried out at the end of each semester to evaluate achievements and plan necessary improvements for future years.